2021
DOI: 10.48550/arxiv.2103.12892
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

$^{22}$Ne Phase Separation As A Solution To The Ultramassive White Dwarf Cooling Anomaly

Simon Blouin,
Jerome Daligault,
Didier Saumon

Abstract: The precise astrometric measurements of the Gaia Data Release 2 have opened the door to detailed tests of the predictions of white dwarf cooling models. Significant discrepancies between theory and observations have been identified, the most striking affecting ultramassive white dwarfs. Cheng et al. (2019) found that a small fraction of white dwarfs on the so-called Q branch must experience an extra cooling delay of ∼ 8 Gyr not predicted by current models. 22 Ne phase separation in a crystallizing C/O white d… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Cheng et al (2019) later demonstrated that about 6 per cent of high-mass white dwarfs ( > 1.05 M ⊙ ) on this transverse sequence, likely the products of double-degenerate mergers, must experience an extra 8 Gyr cooling delay not explained by core-crystallization alone. More recently, Blouin et al (2021) reconciled these results showing that a distillation process during 22 Ne phase separation in crystallising white dwarfs could explain both the cooling delay of standard white dwarfs and the extra delay experienced by high-mass double white dwarf mergers (see also Bauer et al 2020;Camisassa et al 2021). A number of additional studies have focused on the spectral properties of ultra-massive white dwarfs, consolidating the idea that many of these systems are the result of double white dwarf mergers (Hollands et al 2020;Kawka et al 2020;Kilic et al 2021).…”
Section: Introductionmentioning
confidence: 88%
“…Cheng et al (2019) later demonstrated that about 6 per cent of high-mass white dwarfs ( > 1.05 M ⊙ ) on this transverse sequence, likely the products of double-degenerate mergers, must experience an extra 8 Gyr cooling delay not explained by core-crystallization alone. More recently, Blouin et al (2021) reconciled these results showing that a distillation process during 22 Ne phase separation in crystallising white dwarfs could explain both the cooling delay of standard white dwarfs and the extra delay experienced by high-mass double white dwarf mergers (see also Bauer et al 2020;Camisassa et al 2021). A number of additional studies have focused on the spectral properties of ultra-massive white dwarfs, consolidating the idea that many of these systems are the result of double white dwarf mergers (Hollands et al 2020;Kawka et al 2020;Kilic et al 2021).…”
Section: Introductionmentioning
confidence: 88%
“…Note that the integrations at different T are independent from one another and can be performed simultaneously. We have successfully applied this approach to the three-component C/O/Ne mixture found in white dwarf cores [53].…”
Section: Appendix B: Model Partition Functionmentioning
confidence: 99%